Perkembangan Emosional Anak Usia Dini Dalam Lingkungan Keluarga: Emotional Development - Nadiatus Sarifah; Mamun Hanif (Jurnal Inovasi Pendidikan dan Ilmu Sosial, 2025)
This research aims to analyze the influence of parenting styles on the emotional development of early childhood. The main focus of the research is to understand how various types of parenting styles, both democratic and authoritarian, influence children's personality and social behavior. The research method used is a literature review, where data is collected from various literature, scientific articles, and other relevant sources that discuss the relationship between parenting styles and child development. The analysis technique applied is qualitative analysis, which allows researchers to evaluate and interpret data in depth. The research results show that children raised in a democratic parenting style tend to have higher self-confidence, good social interaction skills, and a positive attitude, while children raised in an authoritarian parenting style tend to be more passive, less confident, and have difficulty adapting to social environments. These findings emphasize the importance of creating a positive and supportive family environment for optimal emotional development in children.